Memory and learning in Parkinson disease - Kołodziejczyk, Anna; Tokarski, Stanisław (Studia Psychologica: Theoria et praxis, 2004)
Postreproductive longevity enables the societies to benefit from mature people’s knowledge and experience. Memory is a requisite foundation for human’s cognitive function and progressive changes of the whole mankind. The main aim of the research was to find out how Parkinson’s disease can influence people’s memory and learning process. Parkinson’s disease is also often accompanied by psychical symptoms such as depression, emotional instability and dementia disorders. The basic hypothesis suggested that people suffering from Parkinson’s disease are affected by memory deficits and learning disorders. There were also several detailed hypotheses. During the research people in age between 51 and 83 were examined. They were divided into two groups: the first cohort included 34 people with Parkinson’s disease and the second - 34 healthy people. Research tools (neuropsychological tests) were selected in order to enable wide and precise examination of memory and learning process, and to measure factors that disturb it – depression and dementia disorders. Research hypotheses turned out to be correct in case of: level and frequency of depression disorders, dementia indicator, short-term memory (STM) and long-term memory (LTM) of verbal material logical organized and disabilities of verbal learning. However research didn’t prove that people suffering from Parkinson’s disease are effected by deficits in following cognitive functions: immediate memory of verbal material logical disorganized, STM and LTM of visual retention and learning of nonverbal material.